AGORA VII - working time, training time : Thessaloniki, 7 - 8 October 1999 - (:unkn) unknown (Office for Official Publications of the European Communities, 2003)
Agora VII dealed with the following three topics: work and training in the 21st century; working time and in-company vs. extramural training time; working and training time throughout life. Working and training time are part of social time, which also includes less clearly defined times such as the time devoted to family life, relaxation, leisure, etc. The change of work has strongly influenced the relationship of these different 'times'. The traditional model has been replaced by other approaches, emphasising greater flexibility in work relations, a less linear structuring of social time and a new way of looking at the mutual responsiblities of employers and employees. (BIBB-Doku)
Keywords: G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; I 2.2 Europa; Arbeitszeit; Ausbildungsdauer; Lernzeit; Freizeit; Berufsausbildung; Beschäftigungsform; Sozialkapital; Europa